The Effect of Body Mass Index on Long-Term Patient-Reported Outcome Scores after Anterior Cervical Discectomy and Fusion in an Asian Population: A 2-Year Study - Teo, Shao Jin; Yeo, William; Ling, Marcus Zhixing; Fong, Poh Ling; Guo, Chang Ming; Chen, John Li Tat; Soh, Reuben Chee Cheong (Asian spine journal, 2021)
Study DesignRetrospective cohort study.PurposeThis study aims to analyze the relationship between body mass index (BMI) subjective patient-reported outcomes (PRO) after 1- and 2-level anterior cervical discectomy and fusion (ACDF).Overview of LiteratureThe prevalence of cervical spondylosis and ACDF in expected to continue rising among the aging population of Asia. Moreover, the prevalence of obesity is also increasing. However, limited information is available about the mechanism by which BMI affects PRO after ACDF.MethodsTotal 878 patients underwent ACDF between 2000 and 2015. After excluding patients with previous cervical instrumentation, >2 levels fused, missing BMI measurement, or neoplastic/trauma indication for surgery, 535 patients were included. The PRO measures of the Neck Disability Index, Numerical Pain Rating Scale (NPRS) for Neck Pain, NPRS for Limb Pain, American Academy of Orthopaedic Surgeons–Neurogenic Symptom Score, and Japanese Orthopaedic Association myelopathy score were used. Patients were grouped based on their preoperative BMI, as per the World Health Organization guidelines for Asian populations. PRO scores were collected preoperatively, at 6 months postoperatively, and 2 years postoperatively. A generalized linear model was used to analyze the relationship of BMI category with the individual score, accounting for several factors that are likely to affect the outcomes.ResultsTotal 19 (3.4%) were underweight, 155 (28.0%) were normal weight, 112 (20.3%) were overweight, and 267 (48.3%) were obese. Patients across all BMI categories experienced significant and similar improvements in their postoperative PRO scores. There were no significant differences in the preoperative, 6-month postoperative, and 2-year postoperative PRO scores of the groups. Rate of reoperation was highest in patients with grade II obesity at 8.07%; however, the difference was not statistically significant.Conclusions Irrespective of the BMI, all patients exhibited similar satisfactory outcomes following ACDF. The results support surgery in all subgroups of patients with symptomatic nerve compression in the cervical spine.